Shedding light on the molecular and regulatory mechanisms of TLR4 signaling in endothelial cells under physiological and inflamed conditions - Stierschneider, Anna; Wiesner, Christoph (Frontiers in Immunology, 2023)
Toll-like receptor 4 (TLR4) are part of the innate immune system. They are capable of recognizing pathogen-associated molecular patterns (PAMPS) of microbes, and damage-associated molecular patterns (DAMPs) of damaged tissues. Activation of TLR4 initiates downstream signaling pathways that trigger the secretion of cytokines, type I interferons, and other pro-inflammatory mediators that are necessary for an immediate immune response. However, the systemic release of proinflammatory proteins is a powerful driver of acute and chronic inflammatory responses. Over the past decades, immense progress has been made in clarifying the molecular and regulatory mechanisms of TLR4 signaling in inflammation. However, the most common strategies used to study TLR4 signaling rely on genetic manipulation of the TLR4 or the treatment with agonists such as lipopolysaccharide (LPS) derived from the outer membrane of Gram-negative bacteria, which are often associated with the generation of irreversible phenotypes in the target cells or unintended cytotoxicity and signaling crosstalk due to off-target or pleiotropic effects. Here, optogenetics offers an alternative strategy to control and monitor cellular signaling in an unprecedented spatiotemporally precise, dose-dependent, and non-invasive manner. This review provides an overview of the structure, function and signaling pathways of the TLR4 and its fundamental role in endothelial cells under physiological and inflammatory conditions, as well as the advances in TLR4 modulation strategies. 1 Structure and Function of the Toll-like Receptor 4 and its Receptor Family Toll-like receptors (TLRs) are a family of conserved pattern-recognition receptors (PRRs) that detect and bind to evolutionarily conserved molecular motifs in pathogen-associated molecular patterns (PAMPs) of microbes or damage-associated molecular patterns (DAMPs) of injured tissues to induce innate and adaptive immune response [1-3]. Other classes of PRRs include Nod-like receptors (NLRs), RIG-I-like receptors (RLRs), AIM2-like receptors (ALRs), C-type lectin receptors (CLRs),